ABSOLUTE DATING OF THE MOUND №12 AT THE MYNTOBE BURIAL GROUND (Journal of history-rus, 2024)
Since 2017, the archaeological research has been conducting at the Myntobe burial ground and the adjacent settlementof Kultobe, located in the lower reaches of the Keles River. The research conducted to date, has revealed three types of burial traditions in the necropolis, six construction layers in the settlement and the connection between the necropolis and settlement. In 2023, the excavations were conducted at the mound №12. As a result, “T”-shaped catacomb cemetery was discovered. A skeleton belonging to a young girl was found in the interior of the cemetery (chamber). Due to the moisture of the soil, it turned out that the skeleton was very poorly preserved. Along with the skeleton, torsyk, bowl, a bronze bell and a necklace in the form of a bird were discovered at the mound. These are finds that reflect the worldview and material culture of that time. Objective: The article examines the structure of the mound No.12, the position of the buried skeleton and the burial  traditions of the afterlife in general, determines the absolute dating and is aimed at introducing it into scientific circulation. Scientific novelty: based on the analogues of artifacts found at the burial site, the approximate dating was relatively analyzed with the conclusion of the C14 radiocarbon examination, carried out in “TUBITAK MARMARA” laboratory in the Republic of Turkey and the absolute dating of the burial was determined. Research method: when writing the article, along with the traditional research method, research methods of natural sciences were used. In addition, the drawings were prepared using ArcGis, AutoCad and ArcMap computer graphics programs. Results: The architectural feature of the mound No.12 in the burial ground, burial traditions, material culture and absolute dating were revealed.